Perancangan Sistem Informasi Pemasaran Berbasis Web Pada Pabrik Rokok Herbal Himalaya - Fitri Yana Yana; Budiman Budiman; M. Gugus Azhari (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
In marketing its products, Himalaya cigarette companies have been doing sales promotions in a conventional way. In order for Himalayan herbal cigarette products to be recognized by the wider community, an information technology-based marketing strategy is needed, namely by building a web-based marketing information system. By building an information technology-based marketing strategy, it aims to promote Himalayan herbal cigarette products widely to the public whose access is easier and faster so as to attract consumers to make purchase transactions. The system to be built and developed uses the waterfall method, and for system design using the Usecase method, activity diagrams, class diagrams, and sequence diagrams. The programming.language uses PHP and the database uses Mysql. In order for the results of this research to be easier to access by the public, the implementation of this research design is web-based Keywords: Information System, Marketing, web